Risk factors and outcomes of acute renal infarction - Jihyun Yang; Jun Yong Lee; Young Ju Na; Sung Yoon Lim; Myung-Gyu Kim; Sang-Kyung Jo; Wonyong Cho (The Korean Society of Nephrology, 2016)
Background: Renal infarction (RI) is an uncommon disease that is difficult to diagnose. As little is known about clinical characteristics of this disease, we investigated its underlying risk factors and outcomes. Methods: We performed a retrospective single-center study of 89 patients newly diagnosed with acute RI between January 2002 and March 2015 using imaging modalities. Clinical features, possible etiologies, and long-term renal outcome data were reviewed. Results: The patients' mean age was 63.5 ± 15.42 years; 23.6% had diabetes and 56.2% had hypertension. Unilateral and bilateral involvements were shown in 80.9% and 19.1% of patients, respectively; proteinuria and hematuria were reported in 40.4% and 41.6%, respectively. Cardiovascular disease was the most common underlying disease, followed by renal vascular injury and hypercoagulability disorder. Fourteen patients had no specific underlying disease. At the time of diagnosis, acute kidney injury (AKI) was found in 34.8% of patients. Univariate analysis revealed diabetes mellitus (DM), leukocytosis, and high C-reactive protein (CRP) as significant risk factors for the development of AKI. On multivariate analysis, DM and high CRP levels were independent predictors for AKI. During follow-up, chronic kidney disease developed in 27.4% of patients. Univariate and multivariate Cox regression analyses showed old age to be an independent risk factor for this disease, whereas AKI history was a negative risk factor. Conclusion: DM patients or those with high CRP levels should be observed for renal function deterioration. Clinicians should also monitor for RI in elderly patients.